ANALISIS DAMPAK PINJAMAN MACET TERHADAP PERPUTARAN ARUS KAS PADA KOPERASI MITRA KELUARAGA ANAGATA PARSOBURAN (PERIODE 2020-2023) - Ernika Pasaribu; Zulia Rifda Daulay (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This research method is descriptive quantitative in the form of case study research. This research uses simple linear regression analysis. The data source in this research is the Mitra Keluarga Cooperative, Parsoburan District. Toba Samosir at Head Office. The data collection technique used is a documentary study technique. Based on the results of the regression analysis, the equation obtained is Y = 21.789 + 0.956X. Based on the results of hypothesis testing using the t test by comparing the Sig value with the significant degree used, namely 0.05, the probability value Sig = 0.000 is obtained, which is smaller than the significant degree used (0.000 < 0.05), which means bad loans have a significant effect on turnover. cash flow. With a determinant coefficient value of 32.5% and the remaining 67.5% is influenced by other factors not studied in this research